Vibrational Interventions for Sexual and Pelvic Health: A Randomized Controlled Trial - Brittany L. Roberts; Rebecca G. Rogers; Karissa A. Leong; Caitlin E. Carlton; Cara L. Grimes; Bradley E. Jacobs; Jeanne Ann Dahl; Erin C. Deverdis (Obstetrics & Gynecology, 2026)
OBJECTIVE: To determine whether scheduled vibrator use with an educational handout improves sexual and pelvic floor health for women with sexual dysfunction and pelvic floor disorders than the educational handout alone. METHODS: Randomized controlled trial conducted at a single-site tertiary referral center in the United States. Enrollment occurred from November 2024 to April 2025. Women aged at least 18 years with sexual dysfunction and a pelvic floor disorder diagnosis were included. Participants were randomized to receive either a vibrator approved by the U.S. Food and Drug Administration with scheduled use three times weekly for 8 weeks and an educational handout (vibrator group) or the educational handout, alone (handout group). The primary outcome was sexual function measured by the FSFI (Female Sexual Function Index). Secondary outcomes included results of the SSI (Sexual Satisfaction Index), PISQ-12 (Pelvic Organ Prolapse/Urinary Incontinence Sexual Questionnaire-12), PFDI-20 (Pelvic Floor Distress Inventory-20), F-GUPI (Female Genitourinary Pain Index), and PHQ-9 (Patient Health Questionnaire-9). RESULTS: Of 84 randomized participants, 81 completed the study (41 handout group, 40 vibrator group; 57.9±14.1 years). At 8 weeks, FSFI total scores were significantly higher in the vibrator group (22.2±7.5) than the handout group (16.3±8.7; P =.002), with improvements recorded across arousal, lubrication, orgasm, satisfaction, and pain domains (all P